UR_GERICHTE 2013_OG V 13 16_Tourismusförderung vom 1. Januar 1905 - UR Obergericht (1905)
Art. 29 Abs. 2 BV. Art. 15 Abs. 1 und Art. 19 Abs. 1 lit. a VRPV. Art. 18 Abs. 3 Gerichtsgebührenverordnung. Art. 17 Abs. 2 lit. c TourG. Art. 16 TourR.